2014
DOI: 10.3176/earth.2014.02
|View full text |Cite
|
Sign up to set email alerts
|

Silurian bentonites in Lithuania: correlations based on sanidine phenocryst composition and graptolite biozonation – interpretation of volcanic source regions

Abstract: Integrated correlation of bentonites (altered volcanic ashes) and graptolite biozonation is presented. Detailed study of two Lithuanian drill core sections extended previous knowledge of the occurrence and composition of bentonites to the south. Identification of graptolite species allowed bentonites to be assigned their proper stratigraphical position. Silurian bentonites in Lithuania are mostly characterized by wide and very wide XRD 20 1 reflections of the main component of sanidine phenocrysts. Only fourte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The age of ~433 Ma (Fig. 4D), which is re lated to inher ited zir con cores from the Niewachlów tuffite, can be cor related with the oc cur rence of nu mer ous bentonites in Telychian and Sheinwoodian strata in north west ern Baltica (Kiipli et al, 2013(Kiipli et al, , 2014. This prob a bly cor re sponded to one of the fi nal stages of the Avalonia-Baltica col li sion be tween Llandovery and Wen lock times (De Vos et al, 2010) and in di cates that the base ment rock, where the Niewachlów tuffite magma was gener ated, had been pre vi ously af fected by this col li sion.…”
Section: Polish Tuffites As Part Of Arc-back-arc Magmatic Activity Re...mentioning
confidence: 89%
See 1 more Smart Citation
“…The age of ~433 Ma (Fig. 4D), which is re lated to inher ited zir con cores from the Niewachlów tuffite, can be cor related with the oc cur rence of nu mer ous bentonites in Telychian and Sheinwoodian strata in north west ern Baltica (Kiipli et al, 2013(Kiipli et al, , 2014. This prob a bly cor re sponded to one of the fi nal stages of the Avalonia-Baltica col li sion be tween Llandovery and Wen lock times (De Vos et al, 2010) and in di cates that the base ment rock, where the Niewachlów tuffite magma was gener ated, had been pre vi ously af fected by this col li sion.…”
Section: Polish Tuffites As Part Of Arc-back-arc Magmatic Activity Re...mentioning
confidence: 89%
“…Ac cord ing to Anczkiewicz et al (2017) those bentonites are poorly en riched in in com pat i ble light REEs with a very shal low or ab sent Eu anom aly, with out af fin ity to a subduction zone. Ad di tion ally, the ter mi na tion of colli sion caused an al most com plete ab sence of pyroclastic depos its youn ger than the mid dle Lud low across most of the Bal tic Ba sin area (Fortey et al, 1996;Kiipli et al, 2013Kiipli et al, , 2014. The Niewachlów tuffites are dated as Pøídolí in age (Fig.…”
Section: Tuffites From Poland With Respect To the Magmatism Along The...mentioning
confidence: 99%
“…In order to identify individual eruption layers, researchers have used phenocryst compositions of apatite (Batchelor 2009;Ray et al 2011;Sell & Samson 2011), biotite (Batchelor 2003) and sanidine (Kiipli et al 2007(Kiipli et al , 2010(Kiipli et al , 2011(Kiipli et al , 2012(Kiipli et al , 2014aMännik et al 2014). Separation of phenocrysts for analyses is, however, timeconsuming and often phenocrysts are absent or altered to an extent that they cannot be properly identified.…”
Section: Introductionmentioning
confidence: 99%
“…Bentonites (altered volcanic ashes) in sedimentary sections carry information about tectonomagmatic processes in volcanic source areas (Huff et al 1993; Batchelor & Evans 2000; Kiipli, Soesoo & Kallaste, 2014), directions to volcanic sources (Bergström et al 1995; Kiipli et al 2013), the diagenetic environments of sedimentary rocks (Hints et al 2006, 2008; Somelar et al 2010; Williams et al 2013) and the isotopic ages of rocks (Bergström et al 2008; Cramer et al 2012; Sell, Ainsaar & Leslie, 2013). Recognizing the distinct chemical signatures of eruption layers can lead to exceptionally precise correlations of sections (Emerson et al 2004; Inanli, Huff & Bergström, 2009; Kiipli, Kallaste & Nestor, 2010, 2012; Kiipli et al 2010, 2011; Ray et al 2011; Kiipli, Radzevicius & Kallaste, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some correlations in the East Baltic sections based on sanidine phenocryst compositions were described in the WOGOGOB conference abstract book (Kiipli, Kallaste & Kiipli, 2004). The unusual authigenic mineralogy of Katian bentonites represented by the frequent dominance of chlorite–smectite was discussed in Hints et al (2006) and aspects of the source magma geochemistry in Kiipli, Soesoo & Kallaste (2014). Geochemical evidence indicates vast environmental changes in Late Ordovician time and palaeontological studies have shown strong extinction events (Brenchley, Carden & Marshall, 1995; Harper, Hammarlund & Rasmussen, 2013; Bergström et al 2014).…”
Section: Introductionmentioning
confidence: 99%